T Cell Maturation Stage Prior to and During GMP Processing Informs on CAR T Cell Expansion in Patients - Klaver, Yarne; van Steenbergen, Sabine C. L.; Sleijfer, Stefan; Debets, Reno; Lamers, Cor H. J. (Frontiers in Immunology, 2016)
Autologous T cells were genetically modified to express a Chimeric Antigen Receptor (CAR) directed towards carboxy-anhydrase-IX (CAIX) and used to treat patients with CAIX-positive metastatic renal cell carcinoma. In the present study, we questioned whether the T cell maturation stage in the pre-infusion product affected CAIX CAR expression and function in vitro as well as in vivo CAR T cell numbers and expansion. During the 14 days expansion of CAR T cells prior to administration, we observed shifts from a predominant CD4 to a CD8 T cell phenotype, and from a significant fraction of naïve to central effector T cells. Surface expression of the CAR was equally distributed among different T cell subsets and T cell maturation stages. During T cell culture days 14 to 18 (which covered patient treatment days 1 to 5), T cells demonstrated a decline in CAR expression level per cell irrespective of T cell maturation stage, although the proportion of CAR positive T cells and CAR-mediated T cell effector functions remained similar for both CD4 and CD8 T cell populations. Notably, patients with a higher fraction of naïve CD8 T cells at baseline (prior to genetic modification) or central effector CD8 T cells at 2 weeks of CAR T cell culture demonstrated a higher fold expansion and absolute numbers of circulating CAR T cells at 1 month after start of therapy. We conclude that the T cell maturation stage prior to and during CAR T cell expansion culture is related to in vivo CAR T cell expansion.